Romania : 2008 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Romania. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
The staff report for the 2008 Article IV Consultation of Romania reviews the issues to tighten fiscal policy, putting less of the stabilization burden on the fledgling inflation-targeting framework. GDP growth has remained strong, underpinned by massive capital inflows. Executive Directors observed that large capital inflows related to Romania's accession to the European Union, compounded by procyclical fiscal policies, have contributed to booms in domestic demand and credit and emerging capacity constraints. They recommended that structural reform efforts be relaunched to support per capita income convergence to EU levels.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet